Automatic Billing System for Electric Vehicle Charging (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In battery charging technique the absence of programming and its exploration charging framework that should be grown all things considered. The consequence of the charge estimated in the charging EV can be unique in relation to the charge sum professed to be charged in the charging station. The fact that the charge is estimated independently from one another utilizing its brilliant meters. Furthermore, if mechanical estimations are thought to be precise, it is conceivable to lie in one of the EV or charging station. Likewise, charging data can be controlled. To forestall those issues, this paper proposes the IoT based charging framework. The EV and the charging station store the charging data in the IoT based charging framework after common confirmation and forestall the adjustment. An IoT is a framework wherein all hubs have a similar record, consequently can't be altered in billing. This keeps a client from changing the record subsequent to charging.